(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2021)
The study aimed to assess the macrobenthos abundance and distribution from the Bakkhali River, East Coast of Bangladesh. Macrobenthic and water samples were collected from the upper, middle and lower part of the river during post-monsoon. Several indices were used to find macrobenthos abundance and distribution and their correlation with water parameters were also assessed. Present study identified a total of 628 macrobenthos individuals representing 10 major taxa at three stations where 9 taxa were reported in both upper and middle parts whereas only 7 taxa were observed at lower stream of the river. The highest abundance of macrobenthos (301.04 indivs/m2) was recorded at the lower stream and the lowest abundance (166.3 indivs/m2) was found at the upper part of the river. Macrobenthos distribution showed that the number of Oligochaetes was higher (220 indivs) followed by Nemertinas (169 indivs) and Polychaetes (145 indivs). Study findings reveal that macrobenthos abundance and distribution were comparatively higher at the lower stream than the upper and middle part because of higher level of pollution and sendimentation rate that might influence the macrobenthos abundance and diversity in the upper and middle part. The study also found macrobenthos abundance was proportionally increased with increasing salinity and pH. However, macrobenthos abundance was decreased with increasing temperature. Simpson index (D) was the highest (0.32) at middle and lower part and the lowest (0.23) was in the upper part. Shannon-wiener index (H) was also higher (1.68) at the upper part. Both the indices showed higher diversity at the upper part because of having maximum taxa in the station. Based on the H value, this study reported that Bakkhali River was moderately polluted since H value was in the range of 1.44 to 1.68. These might be because of anthropogenic sources of pollution in the vicinity of the river. This study suggests to take proper management strategies to control aquatic pollution and conserve aquatic biodiversity. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(1), 2021, P 47-55